469. Temporal, Spatial, and Demographic Relationships of SARS-COV-2 Gene Target Cycle Thresholds. (31st December 2020) - Reno, Lisa; Newhart, Donna; Clifford, Robert; Bress, Jonathan; Yu, Stephanie; Hanna, John J; Walsh, Edward E; Lesho, Emil P
Abstract: Background: The optimum duration of isolation precautions (IP) for SARS-COV-2-infected individuals is uncertain. Most healthcare facilities must rely on surrogates of infectivity such as illness duration or nucleic acid amplification (NA). The availability of NA remains limited in many locations, requiring laboratories to alternate platforms to provide uninterrupted support. Regulatory-driven repeat testing further stresses scarce resources. A target gene cycle threshold (Ct) of 24 has been shown to correlate with culture negativity. We sought to evaluate temporal, spatial, and demographic relationships of SARS-COV-2 Ct that could inform local infection control efforts and testing policy. Methods: From 03-14-20 to 06-01-20, nasopharyngeal swabs from inpatients were prospectively tested weekly on an emergency-use authorized laboratory developed assay, or 1 of 3 commercial platforms targeting the RNA-dependent RNA polymerase, N, ORF1ab, S, and/or PanSARS-E genes. A regional COVID-19 registry was also queried. Results: 70 inpatients were prospectively evaluated (Table). Mean time to negative was 28.5 days from symptom onset (SO) and 24.1 days from initial test. Initial Ct values were significantly lower compared to those on week 3 (Figure 1). 3.3%, 8.9%, 31.3% and 50.0% tested negative at weeks 1, 2, 3, and 4 respectively. Trajectories did not differ by race, gender or comorbidity. 13% had isolation precautions (IP) discontinued during admission (mean time to discontinuation 15.8 days; range 12–40). None were linked to new transmissions. 20% reverted to positive after being negative. 0% of a growing number of patients across our health system (27 at time of submission), who have had IP discontinued, were linked to new infections. Data from 180 consecutive patients were available for retrospective evaluation. Mean Ct did not differ between treated-and-released (23.0) and admitted patients (22.6), nor between ward (23.1) and intensive care unit patients (20.2) (all p > 0.4). Table Figure 1 Conclusion: Linear regression revealed that a Ct of 24 and negative Ct value will occur 8.8 and 36 days after SO (Figure 2). These findings are consistent with smaller cohorts, and they add to the growing body of evidence that test-driven approaches for maintenance of IP or patient disposition should be reconsidered. Figure 2 Disclosures: All Authors : No reported disclosures